Validity of Pipelle Endometrial Sampling in Patients with Abnormal Uterine Bleeding: an Analytical Cross-Sectional Study - Shehla Channa, Nazia Haider, Abida Perveen, Mehvish Sumble, Shahneela, Nadia Mehreen (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The study’s objectives were to evaluate the validity of the pipelle device in obtaining a suitable & representative endometrial sample by contrasting the histopathological outcomes of pipelle sampling with those from dilatation and curettage (D&C). Study design: An analytical cross-sectional study Place and Duration: This study was conducted at Liaquat University of Medical and Health Sciences Jamshoro from June 2021 to June 2022 Methodology: The study comprised 100 patients withabnormal uterine bleeding (AUB) who visited the obstetrics and gynecology department’s outpatient clinic. Before a formal D&C, endometrial samples were taken from 100 patients using a pipelle device. The sample marked as sample A was obtained by inserting the Pipelle without conducting cervical dilatation and rotating it inside the uterus. The patients were then brought into the operating room for D&C, and the sample that was taken following D&C was designated as sample B Results: Pipelle sampling exhibited a 97% sensitivity,and a 100% specificity when compared to D&C sampling for obtaining an endometrial sample. With the exception of an endometrial polyp, which could not be detected by the pipelle sample, the Histopathology report’s diagnosis using the sample acquired from the pipelle showed very high sensitivity, specificity, positive predictive value, and negative predictive value. Conclusion: Pipelle endometrial biopsy is a risk-free method of obtaining an appropriate endometrial sample for histopathology. In terms of detecting endometrial abnormalities and endometrial cancer, it has high sensitivity and excellent specificity. An accurate diagnosis of endometrial cancer can be made using a Pipelle endometrial biopsy. Keywords: sampling, endometrial, abnormal uterine bleeding